2009
DOI: 10.1002/ijc.24236
|View full text |Cite
|
Sign up to set email alerts
|

The mannose 6‐phosphate/insulin‐like growth factor II receptor restricts the tumourigenicity and invasiveness of squamous cell carcinoma cells

Abstract: The mannose 6-phosphate/insulin-like growth factor II receptor (M6P/IGF2R) mediates biosynthetic sorting and endocytosis of various factors that impinge on the proliferation, migration and invasiveness of tumour cells. The gene encoding M6P/IGF2R is frequently lost or mutated in a wide range of malignant tumours including squamous cell carcinomas. We have previously shown that M6P/IGF2R-deficient SCC-VII murine squamous cell carcinoma cells secrete large amounts of pro-invasive lysosomal proteinases. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 45 publications
(78 reference statements)
4
36
0
Order By: Relevance
“…4). These results demonstrate that ectopic expression of M6P/IGF2R in FRL14 cells leads to improved intracellular retention of lysosomal enzymes and restoration of dense lysosome formation, as previously shown for receptor-deficient squamous cell carcinoma cells [25].…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…4). These results demonstrate that ectopic expression of M6P/IGF2R in FRL14 cells leads to improved intracellular retention of lysosomal enzymes and restoration of dense lysosome formation, as previously shown for receptor-deficient squamous cell carcinoma cells [25].…”
Section: Resultssupporting
confidence: 85%
“…When the efficacy of physiological proteinase inhibitors was tested, it was found that the potent serine proteinase inhibitor aprotinin had a much weaker effect on cell invasion (22% reduction) than the cysteine proteinase inhibitor cystatin C (49% reduction). We have earlier observed a similar proteinase inhibition profile for the invasive properties of M6P/IGF2R-deficient murine squamous cell carcinoma cells [25]. When FRL14 extracts were immunoblotted with antibodies recognizing rat M6P/IGF2R, it became evident that these cells lack expression of the receptor (Fig.…”
Section: Resultssupporting
confidence: 60%
“…M6P/IGF2R also functions as a growth suppressor, but the loss or mutation of this gene contributes to development and progression of some cancers (15,16) and is involved in HBV-associated hepatocarcinogenesis (17). Moreover, M6P/ IGF2R controls cell adhesion and invasion by regulating αv integrin expression and accelerating uPAR cleavage (18), and restricts the metastatic propensity of squamous cell carcinomas (19). These studies thereby support that M6P/IGF2R may act as the tumor suppressor in carcinogenesis.…”
Section: Introductionmentioning
confidence: 72%
“…They often occur early in carcinogenesis, predisposing to cancer presumably via loss of restraint on IGF2 (Biliya & Bulla 2010). Polymorphisms of IGF2R are also linked to increased risk of oral cancer (Yoon et al 2012), colonic cancer (Probst et al 2009) and HCC (Morcavallo et al 2012) possibly because of impaired IGF2 clearance.…”
Section: Over-expression Of Igf2mentioning
confidence: 99%
“…Loss of IGF2R is associated with a poor prognosis (Jamieson et al 2003, Pavelic et al 2003. The aggressive phenotype may be caused both by excessive IGF2 and over secretion of lysozomal proteases that promote tumour invasion (Probst et al 2009). Conversely, increased IGF2R expression is associated with a better outcome from disease, possibly because of enhanced clearance of IGF2 (Kalla Singh et al 2010b).…”
Section: Receptors and Signallingmentioning
confidence: 99%